(untitled) (Herald of Journalism, 2022)
In the article activity and development of business journalism are analysed in the Kazakh printing. Analysed opinions of researchers of business journalism. Social meaningfulness of business journal- ism is determined on the pages of the republican and regional printing. Key words: economy, business, business journalism, politic, dynamic development.